Isometric training promotes changes in acetylcholinesterase and muscle strength - Rodrigo Rodrigues da Conceição; Roberto Laureano-Melo; Cláudio da Silva Almeida; Alba Cenélia Matos da Silva; Anderson Luiz Bezerra da Silveira; Renato Vidal Linhares; Michelle Porto Marassi; Monica Akemi Sato; Gisele Giannoco; Gabriel Costa e Silva; Wellington Côrtes (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: Isometric strength training (IST) is an important component of different types of sport and others activities of daily life. However, until the present moment, no studies have linked the isometric strength training with acetylcholinesterase (AChE) activity changes. Objective: We evaluated the effects of IST on the muscular AChE activity and strength. Materials and Methods: Wistar rats (n =20) were divided into 2 groups: Control group (Ctr) (sedentary) and trained group (Tr) (submitted to 8 weeks of Isometric strength training). The muscle strength and the acetylcholinesterase activity were evaluated in the solear (SOL) and Extensor Digitorum Longus (EDL) muscles. Results: The body weight of the trained animals was 7.39 % lower than in Ctr rats (p < 0.01) and the EDL weight was 25 % higher (p < 0.05) compared to Ctr. Further, an increase of 30.36 % in strength was observed in the fourth week (p < 0.006) and 26.41 % in eighth week (p < 0.003) of training. In addition, we found an increase of 46.64% in AChE activity in the SOL. In contrast, a reduction of 55.36% in AChE activity in the EDL was observed. Conclusion: Our findings indicate that biochemical, zoometric and functional changes can be evoked by IST with low overload.